2004
DOI: 10.1002/mrm.20285
|View full text |Cite
|
Sign up to set email alerts
|

POCSENSE: POCS‐based reconstruction for sensitivity encoded magnetic resonance imaging

Abstract: A novel method for iterative reconstruction of images from undersampled MRI data acquired by multiple receiver coil systems is presented. Based on Projection onto Convex Sets (POCS) formalism, the method for SENSitivity Encoded data reconstruction (POCSENSE) can be readily modified to include various linear and nonlinear reconstruction constraints. Such constraints may be beneficial for reconstructing highly and overcritically undersampled data sets to improve image quality. POCSENSE is conceptually simple and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
147
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 36 publications
(63 reference statements)
1
147
0
Order By: Relevance
“…The effects of combining SENSE with partial Fourier techniques that employ the POCS and homodyne reconstruction methods have been explored (12). In addition, POCSENSE (13), which uses POCS as an alternative method to reconstruct images acquired with parallel imaging, has been proposed. POCSENSE has the flexibility to incorporate partial Fourier sampling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of combining SENSE with partial Fourier techniques that employ the POCS and homodyne reconstruction methods have been explored (12). In addition, POCSENSE (13), which uses POCS as an alternative method to reconstruct images acquired with parallel imaging, has been proposed. POCSENSE has the flexibility to incorporate partial Fourier sampling.…”
mentioning
confidence: 99%
“…Some initial investigations (13)(14)(15)(16)(17) have explored the use of phase-constrained reconstruction. Here, an estimate of the underlying image phase is used to improve the SENSE reconstruction.…”
mentioning
confidence: 99%
“…Step 1 the combined-channels image is modulated by the coil sensitivity profile of each channel in order to make the combined-channels estimate consistent with the coil data before the data projection in Step 2, which enforces the data consistency constraint for each channel by projecting the current estimate onto the corresponding coil data [28]. In Step 3 data from multiple channels are combined to obtain a combined-channels estimate image.…”
Section: Methodsmentioning
confidence: 99%
“…In view of the independence of the two approaches, combining partial k-space and pMRI should allow further reductions of the data acquisition time [10][11][12][13][14][15][16][17][18]. In fact, recent studies have already demonstrated feasibility of this concept such as techniques combining SENSE and partial Fourier [10][11][12][13][14] and homodyne detection SENSE (HM_SENSE) [11,12], which has been claimed to constitute a robust algorithm. An important aspect of these methods is the estimation of the underlying image phase, which is required for improving the SENSE reconstruction also with regard to the acceleration factor.…”
Section: Introductionmentioning
confidence: 99%